1997
DOI: 10.1091/mbc.8.9.1687
|View full text |Cite
|
Sign up to set email alerts
|

The small GTPase Cdc42 initiates an apoptotic signaling pathway in Jurkat T lymphocytes.

Abstract: Apoptosis plays an important role in regulating development and homeostasis of the immune system, yet the elements of the signaling pathways that control cell death have not been well defined. When expressed in Jurkat T cells, an activated form of the small GTPase Cdc42 induces cell death exhibiting the characteristics of apoptosis. The death response induced by Cdc42 is mediated by activation of a protein kinase cascade leading to stimulation of c-Jun amino terminal kinase (JNK). Apoptosis initiated by Cdc42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
2
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 61 publications
1
67
2
1
Order By: Relevance
“…However, numerous signalling molecules induce apoptosis independently of p53 activity. Interestingly, unlike the situation reported here, the constitutively active form of Cdc42Hs (Cdc42HsV12) signals apoptosis in a p53 independent manner (Chuang et al, 1997).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…However, numerous signalling molecules induce apoptosis independently of p53 activity. Interestingly, unlike the situation reported here, the constitutively active form of Cdc42Hs (Cdc42HsV12) signals apoptosis in a p53 independent manner (Chuang et al, 1997).…”
Section: Discussioncontrasting
confidence: 57%
“…More recently, it has been demonstrated that these proteins are also implicated in apoptosis control (Bazenet et al, 1998;Chuang et al, 1997;Donovan et al, 1997;Fort, 1999 and references therein). Whereas these studies report a role for activated Rho, Rac and Cdc42Hs in apoptosis regulation, we show here that expression of the dominant negative forms of Rac1 and Cdc42Hs are also potent inducers of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these small GTPases are found to mediate apoptosis in a wide-range of cell types. Overexpression of active Cdc42 in Jurkat T lymphocytes induces increased ceramide levels, resulting in cell death [29,30]. Both Rac1 and Cdc42 mediate apoptosis induced by diverse stimuli [31].…”
Section: Introductionmentioning
confidence: 99%
“…Both Rac1 and Cdc42 mediate apoptosis induced by diverse stimuli [31]. It seems that the contribution of Rac1 and Cdc42 to apoptosis is to regulate mainly activa tion of the JNK pathway [32][33][34].…”
Section: Introductionmentioning
confidence: 99%